Audio-Visual-Based Optical Applications as a Media to Improve Students' Understanding of Concepts: A Feasibility Test - Faila, Rohaya Evatri; Solikhah, Nanda Annisa; Setiaji, Bayu (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2023)
One of the learning media by utilizing device technology is realized in the form of an audio-visual physics-based physics mobile learning application called Optically. In the mobile learning application, there are various kinds of content, such as illustrated images, educational videos, sample questions, and practice questions. The research conducted has the aim of (1) producing products in the form of audio-visual physics mobile learning applications on the subject of Diffraction as a learning medium; (2) knowing the feasibility of audio-visual physics-based physics mobile learning applications as a supporting medium for students in understanding the concept of physical optics material. The research and development method uses the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. However, this study is limited only to the development stage (Design). The product feasibility tester in this study was carried out by 17 people who had studied Physical Optics Physics and were studying in the field of Physics. The results of the analysis of the feasibility test of the product carried out, obtained on average on all indicators belonging to the very feasible category.